Modelling the satellite communication links with orthogonal frequency-division multiplexing - Kharchenko, Volodymir; Wang, Bo; Grekhov, Andrii; Leschenko, Anna (Transport, 2016)
Global technologies of data transmission in real time are developing constantly. Therefore, modelling of messages transmission through satellite constellations is an actual problem. In this paper the original model of a communication channel ‘Vehicle-to-Satellite-to-Ground Station’ based on principles of the IEEE 802.11a standard is designed using MatLab Sіmulіnk software. The model allows simulating data transmission with data rate from 6 to 54 Mbit/s using adaptive modulation. Two types of channels were analysed for uplink/downlink modulation – a free space path losses with phase/frequency offset and Additive White Gaussian Noise (AWGN) link. On the base of this model, channel integrity was investigated and dependences of a Signal-Noise Ratio (SNR) on free space path losses, antennas diameters, number of OFDM symbols and satellite transponder noise temperature were received.First published online: 28 Jan 2015